Screening for generalized anxiety disorder (GAD) and associated factors in adolescents and young adults with type 1 diabetes: Cross-sectional results of a Germany-wide population-based study. (February 2022) - Stahl-Pehe, Anna; Selinski, Silvia; Bächle, Christina; Castillo, Katty; Lange, Karin; Holl, Reinhard W.; Rosenbauer, Joachim
Highlights: One in ten adolescents and one in eight young adults had a positive screening result for a generalized anxiety disorder (GAD). More than half of the adult study population with a positive GAD screening result was also screened positive for major depressive disease. Young people screened positive for GAD experienced various impairments. Diabetes-related impairments concerned glycemic control, diabetes-specific quality of life, diabetes distress and treatment satisfaction. Other impairments concerned self-assessed physical performance, sleep quality and social support. Abstract: Aims: The aims of this study were to screen 14- to 30-year-olds with early-onset type 1 diabetes for generalized anxiety disorder (GAD) and to compare the characteristics of the study participants who had a positive result for GAD with those who had a negative result. Methods: This study used data from a questionnaire survey conducted from 2018 to 2019. The GAD-7 questionnaire was used to screen for GAD (positive: GAD-7 score ≥ 10). All regression analyses were adjusted for age, sex, depression diagnosis and considered multiple testing. Results: The 713 participants had a mean GAD-7 score of 4.32 (SD 4.18). A total of 12% of the study population (10% of adolescents, 13% of adults) was screened positive for GAD. Positive screening results were associated with impairments in various domains, such as self-assessed physical performance (RR poor versus good 3.03 [95% CI 1.85–4.96]), difficulty falling asleep (RR ≥3 times/week versus not during the last 4 weeks 5.36 [2.86–10.07]), glycemic control (RR HbA1c per 1 % 1.16 [1.03–1.31]), and diabetes treatment satisfaction (RR poor versus good 2.67 [1.43–5.00]). Conclusions: Diabetologists should be aware that adolescents and young adults with GAD symptoms might experience extensive impairments in their daily lives.